Settling refugees in Australia: achievements and challenges. (2017) - Fozdar, Farida; Banki, Susan
This article examines the extent to which Australia fulfils its legal obligations for resettled refugees. This necessitates noting both the international frameworks that inform the rights accorded to refugees as well as applicable Australian law and policies. But while laws provide us with a point of departure, a thorough analysis of how these laws are upheld requires a focus on the lived experience of settlement, and identification of where law, policy and practice are disjoint and where they conjoin. The paper concludes by noting the opportunities provided by, and limitations of, law and policy, as means to facilitate integration of resettled refugees, and offers some thoughts on how refugee resettlement in Australia might be improved.